Isotopic evidence for nitrification in the Antarctic winter mixed layer. Issue 4 (22nd April 2015) - Smart, Sandi M.; Fawcett, Sarah E.; Thomalla, Sandy J.; Weigand, Mira A.; Reason, Chris J. C.; Sigman, Daniel M.
Abstract We report wintertime nitrogen and oxygen isotope ratios (δ15N and δ18O) of seawater nitrate in the Southern Ocean south of Africa. Depth profile and underway surface samples collected in July 2012 extend from the subtropics to just beyond the Antarctic winter sea ice edge. We focus here on the Antarctic region (south of 50.3°S), where application of the Rayleigh model to depth profile δ15N data yields estimates for the isotope effect (the degree of isotope discrimination) of nitrate assimilation (1.6–3.3‰) that are significantly lower than commonly observed in the summertime Antarctic (5–8‰). The δ18O data from the same depth profiles and lateral δ15N variations within the mixed layer, however, imply O and N isotope effects that are more similar to those suggested by summertime data. These findings point to active nitrification (i.e., regeneration of organic matter to nitrate) within the Antarctic winter mixed layer. Nitrite removal from samples reveals a low δ15N for nitrite in the winter mixed layer (−40‰ to −20‰), consistent with nitrification, but does not remove the observation of an anomalously low δ15N for nitrate. The winter data, and the nitrification they reveal, explain the previous observation of an anomalously low δ15N for nitrate in the temperature minimum layer (remnant winter mixed layer) of summertime depth profiles. At the same time, the wintertime data require a low δ15N for the combined organic N and ammonium in the autumn mixed layer that is available for wintertime nitrification, pointing to intense N recycling as a pervasive condition of the Antarctic in late summer.